2021
DOI: 10.1007/s40122-020-00234-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ultrasound-Guided Erector Spinae Plane Block Combined with Dexmedetomidine on Postoperative Analgesia in Patients Undergoing Modified Radical Mastectomy: A Randomized Controlled Trial

Abstract: Introduction: One of the most common malignancies in women worldwide is breast cancer. Erector spinae plane block (ESPB) can reduce pain after modified radical mastectomy for breast cancer. The duration of nerve block analgesia is limited if local anesthetic agents are used alone. The purpose of this study was to evaluate the effect of dexmedetomidine on postoperative analgesia during a single injection of local anesthetics. Methods: In this double-blind, randomized study, 60 female American Society of Anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 28 publications
(48 reference statements)
1
48
1
Order By: Relevance
“…PONV was insignificantly different between both groups. Wang et al [13] assessed the role of adding dexmedetomidine 1 μg/kg to ESPB compared to ESPB without dexmedetomidine after modified radical mastectomy. Their results agreed ours as they demonstrated that VAS at rest and an active state was significantly lower with dexmedetomidine group at most times of measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PONV was insignificantly different between both groups. Wang et al [13] assessed the role of adding dexmedetomidine 1 μg/kg to ESPB compared to ESPB without dexmedetomidine after modified radical mastectomy. Their results agreed ours as they demonstrated that VAS at rest and an active state was significantly lower with dexmedetomidine group at most times of measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Blocks were performed with a US machine (Sonosite Edge; Sonosite Inc., USA) equipped with an HFL38X high-frequency linear transducer (13)(14)(15)(16). With patients in sitting position, the transducer was positioned longitudinally 3 cm lateral to the T5 spinous process.…”
Section: The Us Guided Espbmentioning
confidence: 99%
“…Craniocerebral surgery is required for brain tumors, severe brain trauma, cranial deformation, encephalorrhagia, and other diseases, which is a common brain surgery, but with a high risk due to the special surgical sites [ 13 15 ]. Before surgery, patients should be routinely examined to select the appropriate anesthesia and surgical methods, mainly including the detection of the cerebral metabolism, intracranial pressure, and cerebral blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Wang et al found that ropivacaine with dexmedetomidine in ESPB for modified radical mastectomy (MRM) was found to decrease VAS and analgesic consumption in the postoperative period when compared to plain ropivacaine without any adjunct. 19 Similar to dexmedetomidine, dexamethasone has also been in used in regional anaesthesia as additive for a very long period of time. 20 Dexamethasone which is a glucocorticoid exerts its action by decreasing perineural edema, decreasing systemic absorption of LA by inducing vasoconstriction and directly acting on nerves to reduce neural discharge and suppressing pain signal transmission.…”
Section: Discussionmentioning
confidence: 99%